2021
DOI: 10.3390/cancers13164137
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Associated with Brain Metastases in HER2-Positive and Triple Negative Breast Cancers

Abstract: Breast cancer (BC) is the most frequent cause of cancer-associated death for women worldwide, with deaths commonly resulting from metastatic spread to distant organs. Approximately 30% of metastatic BC patients develop brain metastases (BM), a currently incurable diagnosis. The influence of BC molecular subtype and gene expression on breast cancer brain metastasis (BCBM) development and patient prognosis is undeniable and is, therefore, an important focus point in the attempt to combat the disease. The HER2-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 118 publications
(166 reference statements)
2
29
0
Order By: Relevance
“…It starts the process by inducing the expression of a mesenchymal phenotype and eventually leads to progression and dissemination [ 20 , 62 , 73 ]. The HER2 / ERBB2 / NEU gene, amplified in 15–35% of BC cancers [ 74 , 75 ], encodes a RTK that activates EMT [ 76 ] as well as the repair of radiation-induced DNA damage [ 77 ]. Another RTK, AXL, was reported to activate EMT and HR even in TNBC cell lines [ 78 ].…”
Section: Dynamic Changes In Dna Damage Responses Are Intricately Link...mentioning
confidence: 99%
“…It starts the process by inducing the expression of a mesenchymal phenotype and eventually leads to progression and dissemination [ 20 , 62 , 73 ]. The HER2 / ERBB2 / NEU gene, amplified in 15–35% of BC cancers [ 74 , 75 ], encodes a RTK that activates EMT [ 76 ] as well as the repair of radiation-induced DNA damage [ 77 ]. Another RTK, AXL, was reported to activate EMT and HR even in TNBC cell lines [ 78 ].…”
Section: Dynamic Changes In Dna Damage Responses Are Intricately Link...mentioning
confidence: 99%
“…It has been shown that TNBC exhibits more traits possessed by CSC than other breast cancer subtypes and is more likely to develop metastases [ 57 , 58 ]. Driven by the aggregation of CD44+ CSC, more CTC clusters and polyclonal metastasis of TNBC were found to be associated with an unfavorable prognosis [ 59 ].…”
Section: Tumor Metastasis In Triple Negative Breast Cancermentioning
confidence: 99%
“…Driven by the aggregation of CD44+ CSC, more CTC clusters and polyclonal metastasis of TNBC were found to be associated with an unfavorable prognosis [ 59 ]. The epidermal growth factor receptor (EGFR) family has been found to be involved in the regulation of cancer metastasis, including TNBC [ 57 , 60 ]. Interactions between the receptor tyrosine kinases EGFR and metastasis with extracellular matrix (ECM)-binding integrins enhance metastatic colonization in model systems [ 60 , 61 , 62 ].…”
Section: Tumor Metastasis In Triple Negative Breast Cancermentioning
confidence: 99%
“…Depending on the expression or lack of certain receptors, tumors can be classified into one of the following three main groups: estrogen/progesterone-receptor-positive (ER+/PR+), human epidermal growth factor receptor 2 positive (HER2+), and triple-negative (TNBC), the latter showing the worst survival rate and, therefore, representing the most aggressive form [14]. Concerning the development of BM, previous studies have shown that patients of the TNBC and HER2+ subtype have a higher risk of developing BM, and several factors associated with BM in HER2-positive and TNBC have been identified [16][17][18][19]. BM development is a complex and multistage process.…”
Section: Introductionmentioning
confidence: 99%